2013
DOI: 10.1186/1742-2094-10-6
|View full text |Cite
|
Sign up to set email alerts
|

Absence of IL-1β positively affects neurological outcome, lesion development and axonal plasticity after spinal cord injury

Abstract: Precise crosstalk between the nervous and immune systems is important for neuroprotection and axon plasticity after injury. Recently, we demonstrated that IL-1β acts as a potent inducer of neurite outgrowth from organotypic brain slices in vitro, suggesting a potential function of IL-1β in axonal plasticity. Here, we have investigated the effects of IL-1β on axon plasticity during glial scar formation and on functional recovery in a mouse model of spinal cord compression injury (SCI). We used an IL-1β deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 43 publications
6
55
1
Order By: Relevance
“…For example, the spinal cord mRNA levels of interleukin-1b (IL-1b) increase 12 hours after SCI; 26 72 hours after injury treated with IL-1 receptor antagonist, the contusion-induced apoptosis was significantly reduced. 27 This result showed that IL-1b is harmful to tissue at the early stage. Macrophages are the main source of IL-1b.…”
Section: Dual Effect Of Macrophages After Scimentioning
confidence: 81%
“…For example, the spinal cord mRNA levels of interleukin-1b (IL-1b) increase 12 hours after SCI; 26 72 hours after injury treated with IL-1 receptor antagonist, the contusion-induced apoptosis was significantly reduced. 27 This result showed that IL-1b is harmful to tissue at the early stage. Macrophages are the main source of IL-1b.…”
Section: Dual Effect Of Macrophages After Scimentioning
confidence: 81%
“…29 Absence of IL-1β inhibits lesion development and axonal plasticity and exerts positive effects on neurological outcome. 30 Blocking the IL-1 receptor suppresses microglial activation, promotes ventral horn neuron survival, 31 attenuates the severity of spinal cord 32 and promotes neurological recovery after SCI. 33 IL-18 is another kind of important proinflammatory cytokine after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that the lower levels of TNF-α and IL-1β we observed 5 d after HI had already started going down, suggesting that we might have missed the peak of release of both cytokines. Higher levels of proinflammatory cytokines are likely to exacerbate brain injury processes, where increased IL-1β and exogenous TNF-α relate to worse outcomes in rodent stroke models (5,38). IL-1β knockout mice demonstrate reduced injury and axonal plasticity after a spinal cord injury (38), and blocking TNF-α offers neuroprotection against inflammatory and excitotoxic insults in neonatal rats (5).…”
Section: Articlesmentioning
confidence: 99%
“…Higher levels of proinflammatory cytokines are likely to exacerbate brain injury processes, where increased IL-1β and exogenous TNF-α relate to worse outcomes in rodent stroke models (5,38). IL-1β knockout mice demonstrate reduced injury and axonal plasticity after a spinal cord injury (38), and blocking TNF-α offers neuroprotection against inflammatory and excitotoxic insults in neonatal rats (5). The anti-inflammatory strategy of using minocycline can reduce levels of TNF-α and IL-1β and protect against HI brain injury in the preterm rat neonate (6).…”
Section: Articlesmentioning
confidence: 99%